2000
DOI: 10.1046/j.1365-3040.2000.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies providing success in a variable habitat: II. Ecophysiology of photosynthesis of Cladophora glomerata

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 23 publications
5
24
0
Order By: Relevance
“…We show here that in L. saccharina, the xanthophyll cycle occurs in situ during the tidal cycle and that its development is directly correlated with the daily course of effective quantum yield. However, the converted pool of violaxanthin is rather low (about 21%) in comparison to the conversion ratio (60%) in Lobophora variegata in coral reefs (Franklin et al 1996), but our data are in agreement with the results obtained during photoinhibition of Cladophora glomerata (Ensminger et al 2000). Harker et al (1999) obtained an in vitro DR of 0.41 when L. saccharina were submitted to 450 µmol quanta m -2 s -1 for 45 min, which caused photoinhibition by suppression of oxygen evolution (Lemoine et al 1995).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We show here that in L. saccharina, the xanthophyll cycle occurs in situ during the tidal cycle and that its development is directly correlated with the daily course of effective quantum yield. However, the converted pool of violaxanthin is rather low (about 21%) in comparison to the conversion ratio (60%) in Lobophora variegata in coral reefs (Franklin et al 1996), but our data are in agreement with the results obtained during photoinhibition of Cladophora glomerata (Ensminger et al 2000). Harker et al (1999) obtained an in vitro DR of 0.41 when L. saccharina were submitted to 450 µmol quanta m -2 s -1 for 45 min, which caused photoinhibition by suppression of oxygen evolution (Lemoine et al 1995).…”
Section: Discussionsupporting
confidence: 89%
“…The rapid recovery of the quantum yield suggested that the responses of Laminaria saccharina to high light intensity are linked to a down-regulation of PSII (now usually termed 'dynamic photoinhibition') rather than to the onset of photosynthetic damage ('chronic photoinhibition'), which reduces photosynthesis for longer periods (Henley et al 1991, Osmond & Grace 1995, Jones & Hoegh-Guldberg 2001, Werner et al 2001. Photoprotection after exposure to solar radiation has been observed in other macroalgae (Hanelt et al 1997, Ensminger et al 2000, Rodrigues et al 2000. It occurs when light energy input exceeds the capacity for energy utilization and usually results in thermal dissipation of excess excitation energy in the pigment antenna of PSII.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In situ photosynthetic performance, reported by quantifying both O 2 -evolution and chlorophyll fluorescence (Henley et al, 1991(Henley et al, , 1992Hanelt et al, 1992Hanelt et al, , 1993Magnusson, 1997;Silva et al, 1998;Ensminger et al, 2000;Häder et al, 2001;Longstaff et al, 2002), have described the occurrence of a photoinhibitory mechanism associated with the noon depression of photosynthetic efficiency followed by an afternoon recovery (Henley et al, 1991;Ensminger et al, 2001;Gévaert et al, 2003), suggesting in some case that daily photoinhibition is the result of UV radiation (Bischof et al, 1998;Häder et al, 2001). However, the extension of photosynthetic depression at noon and the photosynthetic yield (as F v /F m and electron transport rate) have shown to experience seasonal changes (Ensminger et al, 2001), with lower values during summer.…”
Section: Introductionmentioning
confidence: 99%